Civil Society Actors and Broadcast Media Muzzling in Ghana’s Northern Region - & Abdul-Fatawu Shaibu, Amin Alhassan, Felix Odartey-Wellington (Covenant Journal of Communication, 2019)
This work widens the trajectory of research in media ethics and performance in West Africa by examining the role violence plays in the way civil society actors relate with journalists in Ghana’s Northern Region. Findings from in-depth interviews with broadcast stations staff in the region show that they adhere to the principle of self-censorship to avoid attacks, not from the expected sources of overzealous government agents or overbearing media owners, but some civil society actors. The experiences of broadcasters in the Tamale metropolis indicate that the intimidation of journalists on duty is still a common occurrence, their compliance with some ethical principles notwithstanding. One ramification of this is that government agencies and media stakeholders, professional associations, in particular, must wake up to the responsibility of protecting the interests of journalists in all areas, press freedom inclusive.